Management of Velopharyngeal Insufficiency in Cleft Patients With and Without Multidisciplinary Team Care. (April 2021) - Torrecillas, Vanessa; Pollard, Sarah Hatch; McCrary, Hilary; Taylor, Helene M.; Palmer, Alexandra; Meier, Jeremy; Muntz, Harlan; Skirko, Jonathan R.
Objective: To evaluate the effect of an American Cleft Palate-Craniofacial Association (ACPA)–approved multidisciplinary team on velopharyngeal insufficiency (VPI) diagnosis and treatment. Design: Retrospective cohort setting; tertiary children's hospital patients; children with cleft palate repair identified through procedure codes. Main Outcome Measures: Velopharyngeal insufficiency diagnosis was assigned based on surgeon or team assessment. Age at diagnosis and surgery was recorded. Difference in age and rate of VPI diagnosis and surgery was analyzed with t test. Multivariate linear and logistic regression adjusted for confounding variables. Results: Nine hundred forty patients were included with 71.5% cared for by an ACPA-approved multidisciplinary team. More (38.8% ) team care patients were found to have a diagnosis of VPI in comparison to 10% in independent care ( P < .001). Team care was associated with an almost 6-fold increase in VPI diagnosis ( P < .001). Team care was associated with a higher proportion of speech surgery (21% vs 10%, P < .001). Among children receiving team care, each visit was associated with 25% increased odds of being diagnosed with VPI ( P < .001) and 20% increased odds of receiving speech surgery ( P < .001). Age at VPI diagnosis and speech surgery were similar between groups ( P = .55 and .29). Discussion: Team care was associated with more accurate detection of VPI, resulting in more VPI speech therapy visits and surgical management. A higher number of team visits were similarly associated. Conclusion: Further studies of the clinical implication of timely and accurate VPI diagnosis, including quality of life assessments, are recommended to provide stronger guidance on team visit and evaluation planning.